A one-pot four-component synthesis of 3-[(2-amino-4-arylthiazolium-5-yl)(aryl)methyl]-2-oxo-2H-1-benzopyran-4-olates. (2nd September 2020) - Sayadian, Hosna; Yavari, Issa; Halvagar, Mohammad Reza
ABSTRACT: An efficient method has been developed for the synthesis of 3-[(2-amino-4-arylthiazolium-5-yl)(aryl)methyl]-2-oxo-2 H -1-benzopyran-4-olates via a tandem reaction involving 4-hydroxycoumarin, benzaldehydes, thiourea, and 2-bromo-1-arylethan-1-ones, using p -toluenesulfonic acid as catalyst in glacial acetic acid under reflux. The identity of the parent product was confirmed by X-ray analyses while the other similar derivatives were identified by NMR. The good yields of the products, regioselectivity, and lack of metal promoters are the main advantages of this protocol. Highlights The reaction of 4-hydroxycoumarin, thiourea, benzaldehydes, and 2-bromo-1-arylethan-1-ones leads to the formation of functionalized 3-[(2-amino-4-arylthiazolium-5-yl)(aryl)methyl]-2-oxo-2 H -1-benzopyran-4-olates in good yields. GRAPHICAL ABSTRACT: